Human pDCs display sex‐specific differences in type I interferon subtypes and interferon α/β receptor expression. Issue 2 (3rd January 2017) - Ziegler, Susanne M.; Beisel, Claudia; Sutter, Kathrin; Griesbeck, Morgane; Hildebrandt, Heike; Hagen, Sven H.; Dittmer, Ulf; Altfeld, Marcus
Abstract : After stimulation via TLR7 (where TLR is toll‐like receptor), plasmacytoid dendritic cells (pDCs) derived from females have higher mRNA expression levels of all IFNA subtypes and IFNB, as well as higher percentages of IFN‐α‐producing pDCs in comparison to males. The common IFN‐α/β receptor is furthermore expressed at higher levels on pDCs from females in comparison to males. Abstract : The outcomes of many diseases differ between women and men, with women experiencing a higher incidence and more severe pathogenesis of autoimmune and some infectious diseases. It has been suggested that this is partially due to activation of plasmacytoid dendritic cells (pDCs), the main producers of interferon (IFN)‐α, in response to toll‐like receptor (TLR)7 stimulation. We investigated the induction of type I IFN (IFN‐I) subtypes upon TLR7 stimulation on isolated pDCs. Our data revealed a sex‐specific differential expression of IFN‐Is, with pDCs from females showing a significantly higher mRNA expression of all 13 IFN‐α subtypes. In addition, pDCs from females had higher levels of IFN‐β mRNA after stimulation, indicating that sex differences in IFN‐I production by pDCs were mediated by a signaling event upstream of the first loop of IFN‐I mRNA transcription. Furthermore, the surface expression levels of the common IFN‐α/β receptor subunit 2 were significantly higher on pDCs from females in comparison to males. These data indicate that higher IFN‐α production is already established at the mRNA level and propose a contribution of higher IFN‐α/β receptor 2 expression on pDCs to the immunological differences in IFN‐I production observed between females and males.